2006
DOI: 10.1086/504932
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Colonization and Infection With Vancomycin-ResistantEnterococcus faeciumin a French University Hospital

Abstract: An outbreak of infection with vancomycin-resistant Enterococcus faecium occurred at Hotel-Dieu Hospital (Clermont-Ferrand, France). A case-control study was performed in the infectious diseases and hematology units of the hospital. Urinary catheter use (odds ratio [OR], 12 [95% confidence interval {CI}, 1.5-90]; P<.02), prior exposure to a third-generation cephalosporin (OR, 22 [95% CI, 3-152]; P=.002), and prior exposure to antianaerobials (OR, 11 [95% CI, 1.5-88]; P<.02) were independently predictive of vanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Numerous studies have identified antibiotic therapy as a risk factor for VRE acquisition (4,8,(11)(12)(13)(14)(15); however, controversies remain on the association between previous intravenous vancomycin use and VRE carriage (16). We confirmed such an association in univariate analysis, but, like other reports (11,17), we found that the only antibiotic group associated with VRE carriage by multivariate analysis was large-spectrum ␤-lactams.…”
Section: Discussionsupporting
confidence: 80%
“…Numerous studies have identified antibiotic therapy as a risk factor for VRE acquisition (4,8,(11)(12)(13)(14)(15); however, controversies remain on the association between previous intravenous vancomycin use and VRE carriage (16). We confirmed such an association in univariate analysis, but, like other reports (11,17), we found that the only antibiotic group associated with VRE carriage by multivariate analysis was large-spectrum ␤-lactams.…”
Section: Discussionsupporting
confidence: 80%
“…However, after full-text reading 3 more articles had to be excluded, two articles because they did not clearly distinguish between hematology/oncology patients and patients from other medical departments ( Kurup et al, 2008 ) ( Hwang et al, 1998 ) and one article because it described an endemic situation rather than an epidemic setting ( Park et al, 2011 ). Thus, eventually 35 articles ( Böröcz et al, 2005 ; Burnie et al, 2002 ; Chadwick et al, 1996 ; Chlebicki et al, 2006 ; Deplano et al, 2007 ; Edmond et al, 1995 ; Gambarotto et al, 2000 ; Hanna et al, 2001 ; Iosifidis et al, 2012 ; Kawalec et al, 2000 ; Kawalec et al, 2001 ; Kawalec et al, 2007 ; Knoll et al, 2005 ; Lavery et al, 1997 ; Lesens et al, 2006 ; Loeb et al, 1999 ; Marcade et al, 2014 ; McCarthy et al, 2000 ; Montecalvo et al, 1994 ; Nolan et al, 2009 ; Nourse et al, 1998 ; Oh et al, 2004 ; Ozorowski et al, 2009 ; Pendle et al, 2008 ; Rizkalla et al, 1997 ; Rubin et al, 1992 ; Sample et al, 2002 ; Schmidt-Hieber et al, 2007 ; Schuster et al, 1998 ; Singh-Naz et al, 1999 ; Timmers et al, 2002 ; Valdezate et al, 2012 ; Wardal et al, 2014 ; Worth et al, 2007 ; Yoo et al, 2005 ) were considered appropriate for inclusion for further analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In France, the prevalence remains low (Ͻ2%) (12,17). However, an outbreak of VRE was observed in 2004 in the teaching hospital of Clermont-Ferrand (14). Since then, at least five others have been reported in French hospitals (8,15).…”
mentioning
confidence: 99%